INTERNATIONAL LEGAL REGULATION OF GREENHOUSE GAS EMISSIONS AND UKRAINIAN POLICY ON IMPLEMENTATION OF THE KYOTO PROTOCOL - Zubkova, Liubov (European Scientific Journal, ESJ, 2015)
The aim of the report is provide comprehensive analysis of international legal regulation of greenhouse gas emissions limitation and Ukrainian experience in this area. There is a common concern that global warming only makes our world warmer. But it tends to cause substantial climate changes resulting in extreme natural events like droughts, flooding of the coastal territories, powerful hurricanes and abnormal temperatures. By the end of 21st century these changes are expected to put millions of lives in danger. This negative tendency is currently observed in many countries including Ukraine. The Kyoto Protocol is an international agreement linked to the United Nations Framework Convention on Climate Change, which commits its Parties by setting internationally binding emission reduction targets. It is the first agreement between nations to develop global solutions for economic and environmental problems in the 21st century. Analysis of the regulatory instruments regarding global climate change shows that Ukraine still hasn’t adopted the strategic approaches to legislative regulation of greenhouse gas emission. There is no clear policy in the tax assessment, application of excise taxes, environmental taxes, consumer/manufacturer taxes, rate differentiation and other ways of promoting energy efficiency and energy overuse remedies. But the mechanisms of legislative implementation of legal regulation are being designed at this stage.